2021
DOI: 10.1016/j.cogsys.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

When to (or not to) trust intelligent machines: Insights from an evolutionary game theory analysis of trust in repeated games

Abstract: The actions of intelligent agents, such as chatbots, recommender systems, and virtual assistants are typically not fully transparent to the user. Consequently, using such an agent involves the user exposing themselves to the risk that the agent may act in a way opposed to the user's goals. It is often argued that people use trust as a cognitive shortcut to reduce the complexity of such interactions. Here we formalise this by using the methods of evolutionary game theory to study the viability of trust-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Consider an IPD game with misperception such as implementation errors and observation errors 22 , 23 , 31 . Due to the misperception, the parameter in the real game changes from to , and only player X notices the change.…”
Section: Resultsmentioning
confidence: 99%
“…Consider an IPD game with misperception such as implementation errors and observation errors 22 , 23 , 31 . Due to the misperception, the parameter in the real game changes from to , and only player X notices the change.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the above-mentioned behavioural experiments, our mathematical model considers that excluders need to pay a permanent cost of monitoring to identify other players' behaviours during the repeated group interaction process. Indeed, such monitoring cost also called opportunity cost in the previous work [65], has been used to describe the transparency between individuals in game interactions [66]. This realistic set-up makes our model more reasonable and brings a step closer towards understanding how social exclusion strategy works in the realistic case.…”
Section: Discussionmentioning
confidence: 99%
“…We have described how evolutionary modelling and simulations using game theory can be powerful to generate useful insights into the behavioural dynamics and the impact of interventions, in the context of AI development and governance. This approach has been widely adopted to study biological and artificial life systems (Nowak, 2006;Andras et al, 2018;Perc et al, 2017;Smaldino and Lubell, 2014;Han et al, 2021c), which once again has here shown its usefulness to study a complex issue of significant importance.…”
Section: Discussionmentioning
confidence: 99%